Analysis of the Translation of Arabic Texts in the Book of Science: Balaghah Tarjamah Jauhar Maknun by Imam Akhdlori - Gema Mutakabbir; Rinaldi Supriadi; Nunung Nursyamsiah (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
Arabic texts can be understood in their meaning through the process of translation which require specific techniques. Translation techniques will offer resolutions to the translation difficulties encountered by translators. The purpose of this research is to describe the translation techniques from Arabic to Indonesian in the book "Ilmu BalaghahTarjamah Jauhar Maknun" by Imam Akhdlori. This research is qualitative approach and descriptive analysis method. The researchers use literature review method to gather primary data from the SLT and the TLT in the book "Ilmu Balaghah Tarjamah Jauhar Maknun" by Imam Akhdlori, specifically focusing on Chapter One (the state of isnad khabary) and Section One (the meaning of isnad khabary). The data will be analyzed using the 18 translation techniques suggested by Molina and Albir. The data presentation will follow Nida and Taber's translation model. The findings of this research are as follow: In data (1), there are two words with borrowing technique, one word with transposition technique, one word with description technique, one word with common synonym technique, one phrase with reduction technique, and one word with substitution technique. In data (2), there is one word with borrowing technique, one word with transposition technique, one phrase with reduction technique, one word with substitution technique, and one phrase with linguistic amplification technique. In data (3), there is one word with borrowing technique, one phrase with modulation technique, two words with description technique, and one word with substitution technique. In data (4), there is one word with borrowing technique, one word with transposition technique, two words with transposition technique, and one word with linguistic amplification technique. In data (5), there are three words with borrowing technique, one phrase with modulation technique, one word with reduction technique, one word with substitution technique, and one phrase with linguistic amplification technique.